Pengaruh Budaya Organisasi Dan Lingkungan Kerja Terhadap Kepuasan Karyawan Pada PT. Anugerah Pupuk Lestari di Kabupaten Deli Serdang Provinsi Sumatera Utara - Donald Frensius Pasaribu (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to determine the extent to which organizational culture and work environment influence employee satisfaction at PT. Anugerah Pupuk Lestari. Employee satisfaction is a positive feeling employees have toward their work, arising from their evaluation of the work produced. Factors influencing the achievement of satisfaction include organizational culture and work environment, as these can enhance employee satisfaction. The research method employed is descriptive and confirmatory. The data collection technique used involves distributing a questionnaire to 80 respondents. The instruments used were first tested for validity, reliability, and normality, and the statistical method used was path analysis with SPSS version 26 software. The results of the descriptive research conducted on PT. Anugerah Pupuk Lestari employees showed that organizational culture was rated as quite good, the work environment was rated as quite good, and employee satisfaction was rated as quite good. The verifiable results indicate that organizational culture influences employee satisfaction at PT. Anugerah Pupuk Lestari, and the work environment influences employee satisfaction at PT. Anugerah Pupuk Lestari. Therefore, the results show that there is an influence between organizational culture and work environment on employee satisfaction at PT. Anugerah Pupuk Lestari.